East Syriac Theological Instruction and Anti-Chalcedonian Identity in Nisibis in Late Antiquity - Popa, Cătălin-Ştefan ca. 20./21. Jh. (Review of ecumenical studies, 2019)
The School of Nisibis was prominent within the East Syriac tradition. Famous among Eastern Christian alma maters, in this learning center students were educated to become clerics and to propagate a theological identity based upon Theodore of Mopsuestia's legacy, as well as an Anti-Chalcedonian Christology. Focused on different sources, this essay will explore some perceptions against Chalcedon from East Syriac personalities linked to Nisibis from Late Antiquity to the Middle Age. The question lying at the heart of this essay is the following: how influential was the School of Nisibis for the patristic dissemination of Theodore of Mopsuestia's theological position, and implicitly for shaping and defining a dogmatic identity against Chalcedon's dogma and terminology?